UKF-based enhancement and ROS implementation of 4-WDDMR localization with advanced control system. Issue 1 (1st January 2018) - Joukhadar, Abdulkader; Kass Hanna, Dalia
Abstract: This article exhibits integration of nonholonomic four-wheeled differential drive mobile robot platform (4-WDDMR) implemented using an Arduino Mega 2560 microcontroller and robot operating system. Particularly, estimating the current situation of the robot navigation system is complex thanks to uncertainty exerted by the robot incorporated with actuators complexities and nonlinearities. An efficient and accurate estimation technique which applies probabilistic algorithm based Unscented Kalman Filter is proposed. The stability of 4-WDDMR Control-Navigation system has been tested and improved based on Lyapunov criterion. The proposed techniques are implemented and evaluated using MATLAB/SIMULINK®. Both practical and simulation results demonstrate the vitality of the proposed Control-Navigation approach. It is believed that the proposed approaches will help to build an autonomous robotics system that can assist humans with their works in daily life basis.